Differential associations between synthetic endocrine disruptors and renal function impairment across varying degrees in middle-aged and older adult populations - Mu, Junfang; Li, Yajing; He, Lu; Ma, Mingyan; Zhang, Mohan; Wang, Xin; Mao, Danhui (Frontiers in Public Health, 2025)
BackgroundExisting research has revealed that various factors, including environmental pollutants, can affect renal function. This study aims to explore the association between various synthetic Endocrine Disruptors(EDs), which are widely present in the environment, and the renal function of middle-aged and older adult populations.MethodsBased on data from the National Health and Nutrition Examination Survey (NHANES) from 2015 to 2018, a total of 1,199 participants, with a median age of 57 years, who had CKD or at least one CKD complication (such as dyslipidemia, hypertension, diabetes, or hyperuricemia), were included. A comprehensive assessment was conducted on the relationship between 28 synthetic EDs (including perfluoro/polyfluoroalkyl compounds, phosphorus-containing pesticides, and plasticizers) and renal function. Serum concentrations of synthetic EDs were determined using mass spectrometry. Renal function was assessed through urine Albumin-to-Creatinine Ratio (ACR) measurements. The quantile regression models were employed to explore the association between synthetic EDs and renal function. The grouped regression models were used to investigate the differential associations of synthetic EDs with non-CKD and CKD populations.ResultsIn this study, N-perfluorooctanoic acid, MECP phthalate, and Diethylthiophosphate were found to exert damaging effects on renal function. N-perfluorooctanoic acid and MECP phthalate were observed to exhibit differential associations with non-CKD and CKD populations. There was a significant difference in the effect of N-perfluorooctanoic acid between the non-CKD and CKD groups. N-perfluorooctanoic acid was not associated with renal function impairment in the non-CKD group, whereas it exhibited a significant adverse association in the CKD group. There was a significant difference in the effect of MECP phthalate between the non-CKD and CKD groups. MECP phthalate was associated with renal function impairment in the non-CKD group, but not in the CKD group.ConclusionThis study elucidates the associations and differences of synthetic EDs with renal function. Based on the findings, enhanced monitoring and health education regarding environmental exposure to synthetic EDs such as N-perfluorooctanoic acid, MECP phthalate, and Diethylthiophosphate can be implemented to reduce public exposure risks.